Levelling terminological gaps in the Belarusian legislation: questions of theory and practice - Lavitski, Anton A.; Dziadzinkin, Aliaksandr L. (Journal of the Belarusian State University. Philology, 2024)
The article shows the possibilities of modern legal linguistics and, in particular its sub-branch – judicial linguistic expertise, in solving the problem of eliminating legislative gaps. Based on the material prepared by the authors on the instructions of the investigation and inquiry bodies conducting special studies of conflict-prone texts, court decisions published in an open bank as well as dispositions of individual articles of the administrative, civil and criminal codes, proposals for amendments to the Belarusian national legislation are presented. The study substantiates the need to clarify and legally consolidate the definition of verbal extremism as a form of extremism found in the content of speech products, including those generated by software products of imitation of human behaviour. The formulations of the categories of enmity and discord that qualify the crime under art. 130 of the Criminal Code of the Republic of Belarus, as well as the categories of honor, dignity and business reputation, as conceptual components of art. 153 of the Civil Code of the Republic of Belarus are proposed. The necessity of supplementing the wording of art. 188 of the Criminal Code of the Republic of Belarus «Libel» is substantiated: the inclusion of fabrications into the category of slanderous statements as a form of dissemination of knowingly false information in indirect speech acts. It is proposed to extract the characterisation of premeditation from the disposition of art. 10.2 of the Code of Administrative Offenses of the Republic of Belarus as not corresponding to its legal meaning in the formulation of the concept of insult.
Keywords: forensic linguistic expertise; verbal extremism; enmity; discord; insult; threat; libel